PENERAPAN TEKNIK PELAYANAN PRAMUWISATA PADA OBJEK WISATA ISTANA SIAK SRI INDRAPURA - Ningrum, Anisa Cahya; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to find out how the application of tour guide service techniques to the Istana Siak Sri Indrapura tourist attraction. This study uses a qualitative method with a descriptive approach, in which the researcher tries to describe the actual conditions and circumstances by collecting data and information in the field, and explaining them in the form of descriptions. The informants in this study were 5 tour guides and 5 tourists at Istana Siak Sri Indrapura. While the data collection techniques in this study were interviews, observation and documentation. The results of this study indicate that the application of guide service techniques to the Istana Siak Sri Indrapura tourist attraction is not good. not good. And need to be improved again. Keywords: Service Technique Application, Tour Guide, Istana Siak Sri Indrapura